Curcumin Bioactive Substance to Prevent Diabetic Retinopathy Due to Diabetes Mellitus Complications: A Literature Review - Ade Lia Ramadani; Dominikus Raditya Atmaka; Fatqiatul Wulandari; Ratna Kuatiningsari (Universitas Airlangga, 2022)
Diabetes Mellitus is characterized by hyperglycemia, and if it continues, the patients are at risk of having a macrovascular or microvascular complication. One of the most frequent microvascular complications is Diabetic Retinopathy, with a prevalence of 42.6%. Most of the blindness due to Diabetic Retinopathy is a permanent condition and cannot be treated, so prevention is vital in reducing this disease. This literature aimed at providing the recent information related to the effect of curcumin in preventing Diabetic Retinopathy from occurring in patients with Diabetes Mellitus and becoming a source of the latest product innovation in preventing this disease. The writing began by electronic database searching via Google Scholar, Science Direct, Medline, and Research Gate. Only articles in English were taken as a literature review with the following research variables, namely the decrease in ROS (Reactive Oxygen Species), the decline in inflammation, morphological changes in the retina, and reduction in levels of VEGF (Vascular Endothelial Growth Factor)which is an angiogenic factor. Twelve studies showed the following measurement results, namely five studies showed a significant result for giving curcumin extract to decrease ROS; ten studies showed that curcumin extract could significantly improve the morphology of the retina; four studies showed that curcumin extract could significantly help the anti-inflammation process, and four studies showed a significant reduction in VEGF levels. Based on twelve articles reviewed, curcumin can act as a bioactive substance in preventing Diabetic Retinopathy in Patients with Diabetes Mellitus.